Pole semantyczne rzeczownikowej formy αγιασμος w kanonicznych księgach Septuaginty - Kucharski, Jacek (The Biblical Annals, 2017)
The subiect of the present article is the semantic field of the noun form αγιασμος in the canonical books o f LXX. The semantic shades of the term αγιασμος as it is used in these books, are derived and presented by means of a set of linguistic and exegetical methods. The results of the author's research may be brough to the following conclusions. 1. The nominal form αγιασμος appears in the canonic books of LXX nine times in total, of which six of the cases appear in a part of the Greek Bibie which is originally written in Hebrew. The appropriate fragments are: Judg 17, 3; Sir 7, 31; Jer 6, 16; Ezek 22, 8; 45, 4; Amos 2, 11. It also appears once in Sir 17, 10 – the text has been preserved only in Greek, and twice in 2 Macc, namely 2 Macc 2, 17; 14, 36, written straightaway in Greek. 2. The noun is question, as it appears in the biblica books of LXX translated from the Hebrew language does not have an adequate equivalent in the TM of the Hebrew Bible. In the course of the research it has also been proved that in three cases there are derivatires corresponding to this noun and deriving from the stem קדש that is קדש (hi) in Judg 17, 3; קדש in Ezek 22, 8; מקדש in Ezekl 45, 4. In Jer 6,16 it is the term מדגוע, which is derived from the stem רגוע and in Amos 2,11 the word נזיר derived from נזר. 3. The semantic analysis of the LXX-ian texts which contain the term αγιασμος shows that this noun appears as many as six times in a stricctly cultic context, namely in Judg 17, 3; 2 Macc 2, 17; 14, 36; Sir 7, 31; Ezek 22, 8; 45, 4 .4 . It has also been proved here that the nominal form αγιασμος in the canonical books of LXX is used both with people and things. 5. The people who are referred to by means of αγιασμος are the following; God-Jahwe himself (2 Macc 14, 36; Sir 17,10), the Jewish nation |(2 Macc 2, 17); the inhabitants of the capital of the Juda (Jer 6, 16) and nazireats (Amos 2, 11). 6. The shades of the semantic field of the noun αγιασμος when it is used in relation to people are „holiness”, „the state of being made holy”, „sanctification”. Metaphorically, one can also speak of the term αγιασμος as „a temple” or „a holy place”. 7. In the LXX-ian texts, in which the nominal form is used in relation to things, the referents are; silver (Judg 17, 3), the cultic sacrifice made to God (Sir 7,31), and a sanctuary, a temple or a holy place (Ezek 22, 8; 45, 4). 8. When the nouns form αγιασμος is used in relation to things semantic field covers the ensuing shades of meaning: „holiness”, „the state of being made holy”, „sanctification”, „a temple”, „holy place”. When the noun form αγιασμος is used in relation to things, its semantic field covers the ensuing shades of meaning; „holiness”, „the state of being made holy”, „sanctification”, „a temple”, „holy place”. 9. There is a certain clearly-observable regularity in the canonical books of the Greek Bibie of Old Testament, in the texts which contain the nominał form αγιασμος. The point is that in Old Testament the said term is always linked in its meaning with the person of God-Jahwe and speaks of Him that something is His possession (cf. 2 Macc 14, 36; Sir 17, 10) or that something is a result of His activity. What should be strongly emphasized here is that the phenomenon of the abovementioned regularity occurs in all of the previously-presented semantic shedes of αγιασμος  (in particular „holiness”) both with people and things. 10. It seems that within the semantic field of the noun form αγιασμος, there are no particularly essential differences between the semantic shades of the word in books of LXX, which are originally written in Hebrew, and the semantic shades of this word in these books which are written and preserved till our times in Greek.